Perbandingan Efikasi dan Keamanan Vaksin Influenza yang Dilemahkan dan Vaksin Influenza yang Dimatikan pada Anak dengan Asma: Tinjauan Sistematis dan Meta-Analisis: Analisis - Arohid Allatib; Handre Putra; Mahfudz Shidiq; Pedro Purba; Viera Viera (PT Kalbe Farma Tbk., 2025)
Introduction: Asthma patients are at higher risk of experiencing respiratory morbidity due to influenza, vaccination is recommended for this group. This study aims to compare the efficacy and side effects between live-attenuated influenza vaccines (LAIV) and inactivated influenza vaccines (IIV) in asthmatic children. Methods: This research use PRISMA guidelines, with studies sourced from PubMed, Cochrane, and Embase. ROB2 and ROBINS were employed to assess the risk of bias. Quantitative analysis was performed using Review Manager v5.4. Results: A total of 4,753 samples were collected, consisting of 2,390 intervention patients and 2,363 control patients. The meta-analysis results showed that influenza infection was more likely to occur in patients who received the inactivated influenza vaccine [pooled OR = 0.58; 95% CI (0.43, 0.78). Conclusion: The recommended vaccine type is the live-attenuated influenza vaccine, as no significant differences in side effects were observed between the two vaccines.